Pemberian Makanan Pendamping ASI (MP-ASI) Dini Berhubungan dengan Kejadian Stunting pada Anak Balita di Desa Kamal Kabupaten Seram Bagian Barat - Zasendy Rehena (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2021)
Stunting (short body) in toddlers is a manifestation of chronic nutritional deficiency. Stunting in toddlers needs special attention because it can hamper the physical and mental development of children. Stunting is associated with an increased risk of illness and death as well as stunted growth of motor and mental abilities. There are many factors that cause stunting, including giving MP-ASI which is too early for babies, namely 6 months. Children who are given complementary feeding too early are at risk of stunting. The purpose of this study was to determine the relationship between early complementary feeding and the incidence of stunting in under-five children in Kamal Village, West Seram Regency. Methods This research uses descriptive research using a cross sectional design. The study was conducted in December 2020. Sampling was done by purposive sampling method and the number of samples was 80 children under five. The data were analyzed by using the chi square test. The results showed that there was a relationship between early complementary feeding and the incidence of stunting in children under five in Kamal Village with a value of 0,025 0,05. Suggestions to health workers to increase mother's knowledge about giving the right MP-ASI for babies through counseling and training.Â Keywords: Stunting, Complementary Foods for Early Breastfeeding, ToddlersÂ